Carbohydrate utilization and metabolism is highly differentiated in Agaricus bisporus - Patyshakuliyeva, Aleksandrina (BioMed Central, 2013)
BACKGROUND: Agaricus bisporus is commercially grown on compost, in which the available carbon sources consist mainly of plant-derived polysaccharides that are built out of various different constituent monosaccharides. The major constituent monosaccharides of these polysaccharides are glucose, xylose, and arabinose, while smaller amounts of galactose, glucuronic acid, rhamnose and mannose are also present. RESULTS: In this study, genes encoding putative enzymes from carbon metabolism were identified and their expression was studied in different growth stages of A. bisporus. We correlated the expression of genes encoding plant and fungal polysaccharide modifying enzymes identified in the A. bisporus genome to the soluble carbohydrates and the composition of mycelium grown compost, casing layer and fruiting bodies. CONCLUSIONS: The compost grown vegetative mycelium of A. bisporus consumes a wide variety of monosaccharides. However, in fruiting bodies only hexose catabolism occurs, and no accumulation of other sugars was observed. This suggests that only hexoses or their conversion products are transported from the vegetative mycelium to the fruiting body, while the other sugars likely provide energy for growth and maintenance of the vegetative mycelium. Clear correlations were found between expression of the genes and composition of carbohydrates. Genes encoding plant cell wall polysaccharide degrading enzymes were mainly expressed in compost-grown mycelium, and largely absent in fruiting bodies. In contrast, genes encoding fungal cell wall polysaccharide modifying enzymes were expressed in both fruiting bodies and vegetative mycelium, but different gene sets were expressed in these samples.